الحماية الجزائية لحق المتهم في الدفاع أمام القضاء (دراسة مقارنة) - حسن, عبد العزيز (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يعدّ حق الدفاع من قبيل الحقوق الطبيعية، ومن أهم ضمانات المحاكمة العادلة. وهو حق أصيل يحتل مكان الصدارة بين الحقوق الفردية العامة. فهو لم يتقرر لمصلحة الفرد فقط بل لمصلحة المجتمع أيضاً. فلا عدالة عندما لا يكون حق الدفاع كاملاً وحيث يتعذر التثبت من الحقيقة. وتفسير ذلك أن تمكين المتهم من الدفاع عن نفسه لا يعني البتة تهيئة السبيل أمامه للإفلات من العقاب، وإنما يعني التأكيد على ركيزة أساسية للعدالة من شأنها بث الطمأنينة في نفوس الأفراد إلى حسن سير آلياتها في اضطلاعها برسالتها، وهذا من شأنه تبديد أي شكوك حول أية شبهة ظلم حينما يقول القضاء كلمته في إدانة المتهم، كما تمحى مظنة التهاون حين يقضي ببراءته.ولذا يكون البحث في حماية حق المتهم في الدفاع ليس ترفاً فكرياً، لكنه بحث في أدق وأعقد المسائل القانونية عموماً، وهو غوص في الأعماق، مع التمسك بالمشروعية وسط عقبات ليس من السهل تجاوزها. وفي البناء على ما تقدم، نستطيع القول بأن ممارسة المتهم لحقه في الدفاع عن نفسه، تبقى قاصرة عن بلوغ غايتها ما لم تكن محصنة جزائياً. وتمكيناً لممارسة حق الدفاع وحمايته، عمد المشرع الجزائي إلى وضع جملة من القواعد الموضوعية التجريمية والمبرّرة، قاصداً من تكريسها أن يباشر هذا الحق بغير خوف أو وجل. فالمتهم هو أحوج المتقاضين إلى ممارسة حقه في الدفاع تحت مظلة الحماية الجنائية، وهذا يحميه من غدر دفاعه ويضمن حقوقه من الاستغلال لضعف موقفه، وقلة حيلته، واشتداد الصراع في مواجهته. وللوقوف على أوجه هذه الحماية تطرقنا في مبحثين اثنين: الأول كرس لدراسة القواعد الموضوعية التجريمية، أما الثاني فقد خصص لدراسة القواعد الموضوعية المبرّرة. كل ذلك بهدف إظهار أوجه الحماية الجنائية لحق المتهم في الدفاع أمام القضاء.The right of defense can be considered as natural rights, and the most important fair trial guarantees. It is also an inherent right at the center of public individual rights. It has not only created in favor of the individual but also for the benefit of society as a whole. There is no justice when accused people do not have a full right of defense and where not possible to verify the truth. This means that enabling the accused to defend himself does not mean that the punishment is over, but means to emphasize the fundamental pillar of justice that will reassure the individuals to the proper functioning of mechanisms in carrying out its mission, and this would remove any doubts about injustice suspicion when Jurisdiction will announce the accused conviction, also removing the suspicion of complacency while deciding his innocence.Therefore, search in protecting the right of the accused to defend himself is not intellectually luxury, but generally speaking, it is searching in more accurate and the most complex legal issues, it is a dive in the depths, to stick to legitimacy in a centre of obstacles is not easy to overcome. Building on the above, we can say that the accused practice of his right to defend himself, remains inadequate to achieve the purpose if it is not criminally reinforced. And to enable the exercise of the right of accused to defend himself, the penal legislator decided to develop a set of substantive rules incriminating and justified, meaning the dedication of this right to proceed without fear or shame. The accused is in great need to exercise his right of defense under the umbrella of the criminal protection, and this will protect him of the treachery of his defense and ensures that his rights will not be exploited because of the weakness of his position, and the lack of his experience, and the conflict hostile facing him. To find out the aspects of this protection two sections have been developed in this research: the first section devoted to the study of the criminal substantive rules, while the second was created to the study of the justified substantive rules. The aim of this is to show the criminal aspects of protection of the right of the accused to defend in court.